2009
DOI: 10.1590/s1516-84842009005000034
|View full text |Cite
|
Sign up to set email alerts
|

Terapia celular em doenças pulmonares: existem perspectivas?

Abstract: Células-tronco; terapia celular; pulmão; doença pulmonar obstrutiva crônica (DPOC); enfisema; fibrose cística. Introdução: células-tronco e terapia celular Células indiferenciadas que apresentam capacidade de autoduplicação e de dar origem a células diferenciadas são denominadas células-tronco (CT). 1 Melton e Cowan (2004) propuseram uma working definition de CT: "Uma entidade clonal autorrenovável, que é pluripotente e pode dar origem a vários tipos de células diferenciadas". 2 Apesar de variações conceituais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
29

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 59 publications
0
8
0
29
Order By: Relevance
“…Both in humans and in animal models, the literature reports consistent data with evidence for the existence of stained SC from the bone marrow in lungs after bone marrow transplant (Bittmann et al ., 2001;Kotton et al, 2001;Krause et al, 2001;Lama et al, 2007;Ribeiro_Paes et al, 2009;Schrepfer et al, 2007;Suratt et al, 2003;Yamada et al, 2004). At different experimental situations, these and others classical works have shown evidence for the migration of SC to the lung and have provided the theoretical reference which gives grounds for the idea of employing cell therapy in the regeneration of pulmonary tissue.…”
Section: Stem Cells and Cell Therapy: The Rationale For Use In The Lungmentioning
confidence: 96%
See 3 more Smart Citations
“…Both in humans and in animal models, the literature reports consistent data with evidence for the existence of stained SC from the bone marrow in lungs after bone marrow transplant (Bittmann et al ., 2001;Kotton et al, 2001;Krause et al, 2001;Lama et al, 2007;Ribeiro_Paes et al, 2009;Schrepfer et al, 2007;Suratt et al, 2003;Yamada et al, 2004). At different experimental situations, these and others classical works have shown evidence for the migration of SC to the lung and have provided the theoretical reference which gives grounds for the idea of employing cell therapy in the regeneration of pulmonary tissue.…”
Section: Stem Cells and Cell Therapy: The Rationale For Use In The Lungmentioning
confidence: 96%
“…Therefore, it may be concluded that chief characteristic of COPD is the acceleration of functional and morphologic loss, with limitation of gas exchanges, resulting in progressive dyspnea, disability and premature death. Therefore, the development and progression of the pathology are resulting from the interaction of genetic and environmental factors (Ribeiro-Paes et al, 2009). About 1-3% of cases of emphysema are generated by enzyme α1-antitrypsin deficiency, that characterizes a genetic abnormality as an inheritance of autossomal recessive pattern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Desta forma, muitos modelos animais de DPOC têm sido propostos por diferentes grupos de pesquisadores que buscam uma maior compreensão da fisiopatologia, bem como alternativas que sejam eficazes no tratamento do enfisema (Cazzola et al, 2007;Faria et al, 2012;Fusco et al, 2002;GOLD, 2009;Gross et al, 1965;Hele, 2002;Hyatt et al, 2000;Longhini-dos-Santos et al, 2013;Mahadeva, Shapiro, 2002;Martorana et al, 1989;Nikula et al , 2000;Ribeiro-Paes et al, 2009, 2011, 2012.…”
Section: )unclassified